Frequency control strategy of microgrid distributed virtual synchronous generator based on asynchronous event triggered communication protocol - HE Ping; ZHU Yongliang; TAO Yukun; LIU Xinyan; SHAO Jingjing (International Journal of Electrical Power & Energy Systems)
Virtual Synchronous Generator (VSG) control technique is a potent solution to the issue of insufficient inertia in power systems. To address the challenges of low inertia and low output impedance in microgrids, this paper proposes a VSG frequency distributed collaborative secondary control strategy and develops a distributed active power sharing control strategy. Initially, considering the frequency parameter discrepancies among individual VSG, a tracking controller for the VSG frequency reference model is designed based on the heterogeneous multi-agent theory. Subsequently, to alleviate the communication overhead, an integral-type event triggering mechanism is constructed. This mechanism obviates the need for a time synchronization system in VSGs, allowing each unit to rely solely on its internal clock for periodic triggering condition assessments. In contrast to the existing VSG secondary control strategies, this approach ensures the efficacy of the distributed secondary control strategy amidst asynchronous communication networks. Furthermore, the stability of the proposed secondary control strategy is demonstrated using the Lyapunov function in conjunction with the event triggering mechanism. Ultimately, an island microgrid system is simulated on the MATLAB/simulink platform, and the simulation results verify the feasibility and effectiveness of the proposed control strategy.